Soil phosphorus fractionation in Icelandic long-term grassland field experiments - Þorsteinn Guðmundsson 1948-; Sigurður Þór Guðmundsson 1977-; Guðni Þorvaldsson 1952- (2014)
Long-term fertiliser experiments on hayfields at Sámsstaðir, South Iceland, and Hvanneyri, West Iceland, provided the basis for investigations on phosphorus fractions, the fate of P fertilisers and P sorption in Icelandic soils. Total (Pt), inorganic (Pi), organic (Po), ammonium oxalate extractable (Pox), ammonium lactate extractable (PAL) and anion resin extractable (Pan) fractions were determined. The P sorption was measured and P sorption maximum (Smax) calculated. Ammonium oxalate extractable Si, Al and Fe were measured and the degree of P saturation (DPS) was calculated. We found all surplus applied P in the top 10 cm of the soil with the highest increase in the top 5 cm. While there was only a slight increase in Po, most of the surplus P was inorganically bound, with a strong correlation between Pt, Pi and Pox. Phosphorus saturation (Smax) was highly correlated with oxalate extractable Si and Al in the dry Silandic Andosol. However, in the Histic Andosol it was only highly correlated with Feox and not to Alox, indicating a different behaviour relating to redox conditions. Available P (PAL) increased with increasing P application mainly in the top 5 cm, but was not detectable at 10-20 cm depth. There was a good correlation between PAL and the degree of phosphorus saturation which only reached critical level in the top 5 cm with the highest P application of 39 kg ha-1 year-1. Water soluble Pan was substantially higher than PAL indicating that the phosphorus that had accumulated in the soil could be released and may be a useful source of P in future. Jarðvegur úr langtímatilraunum á túnum á Sámsstöðum og á Hvanneyri var notaður til að kanna bindingu og afdrif áborins fosfórs í íslenskum jarðvegi. Heildarmagn fosfórs (Pt) í jarðveginum var mælt og skipting fosfórsins í ólífræn sambönd (Pi) og lífræn (Po). Einnig var mælt hversu mikið losnar af P í ammóníum oxalati (Pox), ammóníum laktati (PAL) og með anjóna resin (Pan). Binding fosfórs var greind og hámarks aðsog (Smax) reiknað með Langmuir líkingunni. Si, ...